COVID‐19 pandemic: Challenges and solutions from the cardiology pharmacist's perspective. Issue 6 (17th August 2020) - Pickworth, Kerry K.; Blais, Danielle; Bagnola, Aaron; Barcelona, Robert; Boyd, J Michael; Brink, Heidi; Chilbert, Maya; Galipeau, Daniel; Gengler, Brooke; Gerlach, Anthony T.; Hayes, Charles; Jacobs, Joshua; et al.
Abstract: The recent coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) challenges pharmacists worldwide. Alongside other specialized pharmacists, we re‐evaluated daily processes and therapies used to treat COVID‐19 patients within our institutions from a cardiovascular perspective and share what we have learned. To develop a collaborative approach for cardiology issues and concerns in the care of confirmed or suspected COVID‐19 patients by drawing on the experiences of cardiology pharmacists across the country. On March 26, 2020, a conference call was convened composed of 24 cardiology residency‐trained pharmacists (23 actively practicing in cardiology and 1 in critical care) from 16 institutions across the United States to discuss cardiology issues each have encountered with COVID‐19 patients. Discussion centered around providing optimal pharmaceutical care while limiting staff exposure. The collaborative of pharmacists found for the ST‐elevation myocardial infarction patient, many institutions were diverting COVID‐19 rule‐out patients to their Emergency Department (ED). Thrombolytics are an alternative to percutaneous coronary intervention (PCI) allowing for timely treatment of patients and decreased staff exposure. An emergency response grab and go kit includes initial drugs and airway equipment so the patient can be treated and the cart can be left outside the room. Cardiology pharmacists have developed policies and procedures to address monitoring of QT prolonging medications, the use of inhaled prostacyclins, and national drug shortages. Technology has allowed us to practice social distancing, while staying in close contact with our teams, patients, and colleagues and continuing to teach. Residents are engaged in unique decision‐making processes with their preceptors and assist as pharmacist extenders. Cardiology pharmacists are in a unique position to work with other pharmacists and health care professionals to implement safe and effective practice changes during the COVID‐19 pandemic. Ongoing monitoring and adjustments are necessary in rapidly changing times.